Pengaruh Edukasi Menstruasi Menggunakan Media Video Animasi dan Leaflet Terhadap Kesiapan Menarche pada Anak Usia 9-12 Tahun di SDN Bojong 2 Cianjur - Zahra Ismi Fauziah; Siti Kamillah; Weslei Daeli (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Background: For women, menarche is the first menstruation, which is a sign of puberty (maturity) for healthy adolescents. Menarche occurs at the age of 8 to 12 years. It is very important to prepare adolescents mentally and psychologically from the beginning of menarche so that they have a positive response to menarche. Aspects of menarche readiness are divided into 3, namely aspects of understanding, aspects of appreciation, and aspects of willingness. Factors that influence menarche readiness include internal factors, namely attitude and age, while external factors are sources of information, maternal social support and social environment. Unpreparedness to face menarche has an impact on personal hygiene during menstruation and anxiety. Objective: To determine the effect of menstruation education using animated video media and leaflets on menarche readiness in children aged 9-12 years at SDN Bojong 2 Cianjur. Method: This study used a true experimental design research design, with a pretest-posttest with control group design. The sampling technique used total sampling with a sample size of 94 respondents. Data collection was carried out using a questionnaire, then the data was processed and analyzed using SPSS computer software. Statistical test using Wilcoxon test. Results: In the intervention group between the pretest and posttest values ​​obtained a p-value of 0.000 (<0.05), while in the control group between the pretest and posttest values ​​obtained a p-value of 0.084 (> 0.05). Conclusion: There is a significant difference between the intervention group and the control group after being given menstruation education. So there is an effect of menstruation education using animated video media and leaflets on menarche readiness in children aged 9-12 years at SDN Bojong 2 Cianjur.